Added value of multiparametric MRI for diagnosing subcentimeter functional adrenal nodules in primary aldosteronism using CXCR4-targeted PET/MRI. - Meng, Xiaoli; Quan, Zhiyong; Fan, Linni; Zhang, Mingru; Li, Guiyu; Xu, Mengwei; Wang, Jia; Ma, Wenhui; Yang, Weidong; Yang, Bo; Wang, Jing; Kang, Fei (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Objective: This study aims to evaluate the clinical utility of 68Ga-pentixafor PET/MRI in diagnosing primary aldosteronism (PA) in functional adrenal nodules, with a particular focus on subcentimeter nodules. Additionally, the diagnostic performance of integrated PET/MRI is compared to single-modality PET imaging. Methods: A total of 62 patients with clinical suspicion of PA were enrolled from a tertiary hospital in China. Prior to adrenalectomy, all patients underwent 68Ga-pentixafor PET/MRI, followed by CXCR4 and CYP11B2 immunohistochemical analysis post-surgery. Adrenal lesions were stratified into two size groups: ≥ 1 cm and < 1 cm. Quantitative PET parameters, including SUVmax, SUVmean, and lesion-to-liver uptake ratio (LLR), were evaluated alongside MRI parameters such as outphase/inphase signal ratio (OIR), relative percent washout (RPW), T2-weighted image intensity, apparent diffusion coefficient (ADC). Receiver operating characteristic (ROC) curve analysis was performed to establish diagnostic thresholds. Comparative analyses were conducted between single-modality PET and integrated PET/MRI for diagnostic accuracy. Results: Among 62 patients, 74 adrenal lesions were confirmed pathologically, comprising 37 aldosterone-producing adenomas (APA, ≥ 1 cm), 21 aldosterone-producing micronodules (micro-APA, < 1 cm), and 16 non-functioning adenomas (NFA). Key PET/MRI parameters, including SUVmax, SUVmean, LLR, OIR, and RPW, showed significant differentiation between functional adrenal nodules and normal adrenal glands (P < 0.001). For nodules ≥ 1 cm, the PET SUVmax threshold of 7.87 achieved a sensitivity of 92.3% and specificity of 95.0% for APA diagnosis. For nodules < 1 cm, the PET SUVmax threshold of 6.49 yielded a sensitivity of 68.8% and specificity of 83.3% for micro-APA diagnosis. Integrated PET/MRI significantly improved the diagnostic sensitivity for PA subcentimeter nodules from 68.8% (with PET alone) to 87.5%, and increased the area under the ROC curve from 0.760 to 0.854, with no significant reduction in diagnostic specificity. Conclusion: 68Ga-Pentixafor PET/MRI demonstrated high diagnostic accuracy for functional adrenal nodules in PA, particularly enhanced sensitivity for subcentimeter nodules compared to PET alone.